Pelaksanaan Pemilu Sebagai Wujud Demokrasi Pancasila Di Indonesia - Ana Saritilawa; Anna Rahmadia; Sasmi Nelwati (International Forum of Researchers and Lecturers, 2024)
General elections (elections) in Indonesia are an important mechanism in the democratic process which aims to elect people's representatives and government leaders directly by the people. This research aims to examine the principles, objectives of the election administration system, and the election system implemented in Indonesia. Using a descriptive and analytical approach, this study explores various aspects related to elections in Indonesia, including the basic principles underlying their implementation, the objectives to be achieved, and the electoral system used. This research concludes that although the electoral system in Indonesia has run with strong democratic principles, there is still room for improvement in its implementation and supervision. Recommendations include increasing political education for the community, strengthening election management institutions, and stricter law enforcement against election violations. With these steps, it is hoped that elections in Indonesia can be more effective, fair and democratic, so that they are able to fully reflect the will of the people.